SOCIOLINGUISTIC AND GEOLINGUISTIC APPROACHES TO THE HISTORICAL DIFFUSION OF LINGUISTIC INNOVATIONS: INCIPIENT STANDARDISATION IN LATE MIDDLE ENGLISH - Hernández Campoy, Juan Manuel; Conde Silvestre, Juan Camilo (International Journal of English Studies, 2009)
The diffusion of linguistic innovations and changes has become a common object of sociolinguistic and geolinguistic research. As such, the process has been studied from four complementary perspectives: (a) the communicative or interpersonal, (b) the time dimension, © the social perspective and (d) the geographical or spatial. Despite the successful application of these methodologies to tracing the diffusion of innovations in progress and recently attested changes, attention is hardly ever given to reconstructing these four dimensions in connection with the diffusion of changes in the past. In this paper we consider the possibility of applying these methods and findings to the different faeets of the diffusion of a weIl attested change in the history of English: the spread of incipient standard spellings from London in the late Middle English period. Particular attention is given to the unfolding of this process in the course of time, its diffusion across social ranks and networks, as well as to its possible geographical circulation.